Follow-up for 3 years of a pediatric population diagnosed in 2018 with mother-to-child transmission of HIV in 8 Latin American countries in the PLANTAIDS cohort - Beatriz Álvarez Vallejo; Alicia Hernanz Lobo; Itzíar Carrasco García; Tomás Bruno Pérez; Greta Mino-Leon; Judith Rosabel Soffe Pazmiño; Julio Werner Juarez Lorenzana; Tatiana Drummond; Noris Marlene del Socorro Pavía Ruz; María del Rocío Muñoz Hernández; Dulce María Morales Pérez; Dora Estripeaut; et al. (BMC Infectious Diseases, 2024)
Abstract Introduction The frequency of mother-to-child transmission (MTCT) of human immunodeficiency virus (HIV) in Latin America has decreased considerably. However, new infections continue to be recorded, and the pediatric population remains one of the most vulnerable groups in this region. The main objective of the study was to describe the clinical, epidemiological and psychosocial characteristics of new diagnoses of HIV MTCT in 2018 in the PLANTAIDS network (Paediatric Network for Prevention, Early Detection and Treatment of HIV in Children) during the 3 years following diagnosis. Methodology Retrospective, multicenter, descriptive study based on a 3-year follow-up of patients diagnosed with HIV infection due to MTCT in 2018 in 10 hospitals in 8 Latin American countries (Costa Rica, Ecuador, Mexico, Honduras, El Salvador, Panama, Guatemala and Venezuela). The hospitals belonged to the PLANTAIDS network, which is included in CYTED (Ibero-American Programme of Science and Technology for Development). Results The study population comprised 72 pediatric patients (38.9% male). The median age at diagnosis was 2.4 years (IQR: 0.8–5.4). There were 35 cases of opportunistic infections corresponding to 25 patients (34.7%), with tuberculosis being the most common. Adequate childhood vaccination coverage was achieved in 80.5%. There were 3 cases of acute SARS-CoV-2 infection, and these were asymptomatic or mildly symptomatic. According to the Centers for Disease Control and Prevention (CDC) classification, the most frequent clinical-immunological stage at all check-ups was C1. Three patients died from opportunistic infections and/or advanced HIV infection. Conclusions It is important to diagnose HIV infection early in pediatrics, since early initiation of ART is associated with a decrease in mortality. Despite this, HIV infection has a poor prognosis in children, necessitating adequate follow-up to ensure adherence to health care and ART, although it can sometimes prove difficult in children.